2016
DOI: 10.1038/nature17195
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cycling of reactive nitrogen in the marine boundary layer

Abstract: Nitrogen oxides are essential for the formation of secondary atmospheric aerosols and of atmospheric oxidants such as ozone and the hydroxyl radical, which controls the self-cleansing capacity of the atmosphere. Nitric acid, a major oxidation product of nitrogen oxides, has traditionally been considered to be a permanent sink of nitrogen oxides. However, model studies predict higher ratios of nitric acid to nitrogen oxides in the troposphere than are observed. A 'renoxification' process that recycles nitric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
325
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(359 citation statements)
references
References 44 publications
30
325
4
Order By: Relevance
“…We find HONO is most important near urban areas close to the surface (<100‐m altitude) over land, contributing <8% to the projected daily radical budget within the MBL, which was typically well mixed from the surface to ~1 km. Our measurements show some support for slower daytime production of HONO from pNO 3 − photolysis than reported by Ye et al () and more broadly consistent with that presented in Romer et al (). We thus conclude that daytime HONO production and contribution to primary radicals remain uncertain, but is likely smaller than previous estimates would have suggested.…”
Section: Discussionsupporting
confidence: 92%
“…We find HONO is most important near urban areas close to the surface (<100‐m altitude) over land, contributing <8% to the projected daily radical budget within the MBL, which was typically well mixed from the surface to ~1 km. Our measurements show some support for slower daytime production of HONO from pNO 3 − photolysis than reported by Ye et al () and more broadly consistent with that presented in Romer et al (). We thus conclude that daytime HONO production and contribution to primary radicals remain uncertain, but is likely smaller than previous estimates would have suggested.…”
Section: Discussionsupporting
confidence: 92%
“…The linear relationship between HONO production rate and the product of particulate nitrates and its photolysis was recently confirmed by Ye et al (2016b) in the marine boundary layer, where this mechanism plays an important role in recycling NO x . While there is still some debate about the absorption cross section of surface-adsorbed HNO 3 / nitrate, Ye et al (2016a) report that the photolysis of HNO 3 / nitrate is 1 to 3 orders of magnitude faster than that of gas-phase HNO 3 , confirming that this process is a significant source of HONO in many environments.…”
Section: Introductionmentioning
confidence: 81%
“…HONO chemistry can also play a significant role in the recycling of NO x , as recently demonstrated by Ye et al (2016b).…”
Section: Introductionmentioning
confidence: 87%
“…the DLR Falcon, Geophysica, NASA Global Hawk, NSF/NCAR C-130) and high-flying balloon (LPMA/DOAS and MIPAS/TELIS/mini-DOAS payload) observations (Ferlemann et al, 2000;Weidner et al, 2005;Kritten et al, 2010;Prados-Roman et al, 2011;Kreycy et al, 2013;Gratz et al, 2015;Ye et al, 2016;Stutz et al, 2017;Werner et al, 2017). The major design criteria for airborne measurements are a small weight (several to tens of kilograms), a small power consumption (200 W), multiple channels of moderate spectral resolution (i.e.…”
Section: Instrument Descriptionmentioning
confidence: 99%
“…The airborne limb measurements of scattered skylight continued with the aircraft studies of Prados-Roman et al (2011) made from aboard the DLR Falcon and more recently from the American High-performance Instrumented Airborne Platform for Environmental Research (HIAPER) aircraft , the NSF/NCAR C-130 (Gratz et al, 2015;Ye et al, 2016), the NASA Global Hawk Werner et al, 2017), and those reported here from HALO, an aircraft based on a Gulfstream G550 jet (http://www.halo.dlr.de/). For first results from measurement campaigns involving the HALO mini-DOAS instrument, the reader is referred to e.g.…”
Section: Introductionmentioning
confidence: 99%